PENGARUH MODEL LEARNING CYCLE 5E DENGAN E-LKPD BERBASIS MULTIREPRESENTASI TERHADAP SCIENTIFIC REASONING SISWA SMP - Setiyawati, Zeni; Supeno, Supeno; Ridlo, Zainur Rasyid (Edukasi: Jurnal Pendidikan, 2023)
Scientific reasoning is one of the important skills students and graduates need today. Scientific reasoning is part of high-level thinking skills and is one of the skills required in school curriculum implementation. Even though it is an important skill, research data shows that students' scientific reasoning is still unsatisfactory. The purpose of this study is to examine how junior high school students' scientific reasoning is affected when the 5E learning cycle model and multi-representation-based E-LKPD are used to execute learning. The study was carried out during the even semester of the 2022–2023 school year at SMP Negeri 2 Panti. Students in classes IX B and IX E served as the research samples, while all IX students comprised the study's population. The study used the quasi-experimental design method in conjunction with a quantitative methodology. Examinations, observations, interviews, and documentation were used to gather research data. Research data was analyzed by applying several tests, including the N-gain test, the normality test using Shapiro-Wilk, and the independent sample t-test. The research results show that implementing the 5E learning cycle model using multi-representation-based E-LKPD positively influences and impacts the scientific reasoning of students.